2012
DOI: 10.1080/14999013.2012.723664
|View full text |Cite
|
Sign up to set email alerts
|

Violent Female Offending: An Exploration of Repeat and One-Time Offending

Abstract: There has been an increased focus on understanding the factors that may be predictive of violent recidivism among female offenders. Previous research has indicated that repeat and one-time violent female offenders have very different profiles. All female prisoners incarcerated for a violent offense in Scotland over a two-month period (n = 87) were compared on a range of demographic, offending, behavioral and mental health variables. Multivariate regression analysis revealed a lack of 'spousal' relationships an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…As shown in Table 1, women on parole had more evidence of violence than women on probation. Finally, because some past research has treated this type of composite score of violence as a categorical variable, we also followed the practice of prior studies that compared women with zero, one, and two or more indicators of violence (Bell, 2004; Kubiak et al, 2013; Mahoney & Karatzias, 2012; Pollock et al, 2006; Verona & Carbonell, 2000).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table 1, women on parole had more evidence of violence than women on probation. Finally, because some past research has treated this type of composite score of violence as a categorical variable, we also followed the practice of prior studies that compared women with zero, one, and two or more indicators of violence (Bell, 2004; Kubiak et al, 2013; Mahoney & Karatzias, 2012; Pollock et al, 2006; Verona & Carbonell, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…For a sample of women on probation and parole, our aim is to describe the nature of violence and to identify the characteristics of the women who use violence. Prior studies have found differences between one-time and repeatedly violent women (Bell, 2004; Kubiak et al, 2013; Mahoney & Karatzias, 2012; Pollock et al, 2006; Verona & Carbonell, 2000); thus, we compare women with zero, one, and multiple indicators of violence. We also examine our measure of violence as a quantitative variable in which higher numbers indicate stronger indication of violence.…”
Section: Research Questionsmentioning
confidence: 99%
“…Although any improvements are welcomed, it is important for a more complete range of improvements to be realized. A greater focus in relational functioning may also lead to wider and more robust outcomes (Ford et al, 2013; Mahoney & Karatzias, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This review has identified four publications that report on the efficiency and effectiveness of psychological therapies for women with ID and offending behaviours. All studies focused on group interventions using CBT (Mahoney & Karatzias ). A potentially biasing limitation of all the studies related to the failure to control for concurrent treatment that participants received.…”
Section: Discussionmentioning
confidence: 99%